Associations of house characteristics with indoor dampness and measured moisture: Results from three New Zealand House Condition Surveys in 2005, 2010 and 2015. (15th January 2022) - Taptiklis, Phoebe; Phipps, Robyn; Jones, Mark; Douwes, Jeroen
Abstract: Associations between house characteristics and inspector-assessed subjective indoor dampness (yes/no) and measured floor and ceiling joist timber moisture were measured, using the 2005, 2010 and 2015 New Zealand House Condition Surveys, involving 1572 timber-framed houses. We conducted logistic (dampness) and linear regression (moisture) for each survey separately and mutually adjusted for other house characteristics (ventilation, insulation, subfloor defects, building envelope condition (BEC) defects, tenure, number of occupants), climate zone (latitude), rainfall and outdoor temperature. The odds of subjective damp increased with: more BEC defects (p for trend <0.001), with adjusted odds ratios (aORs) of 3.9–9.6 (p < 0.001) across surveys for houses with 4 or 5 (of 5) defects, compared with houses with ≤1 defect; more subfloor defects (p for trend <0.01 for 2010 and 2015 surveys); less ventilation (p for trend <0.05 for 2010 and 2015 surveys); less insulation (p for trend ≤0.05 for 2010); and increased occupancy (aORs 1.2–2.3, for ≥5 occupants compared to 1–2, not significant). Dampness was more common in rental houses (aORs 1.6 to 2.2, p < 0.05 in 2015). Floor joist moisture content was higher in houses with more subfloor (1.2%–1.9% increase per defect, p for trend ≤0.01) and BEC defects (1.5%–1.8% for houses with 4–5 defects, p < 0.001 for 2005 and 2015 surveys). In conclusion, subfloor and building envelope defects were associated with both inspector-assessed dampness and objectively measured moisture in floor joists. Less insulation, ventilation and higher occupancy were associated with increased subjective dampness but not with measured moisture. Highlights: Building envelope condition is associated with both subjective dampness and measured moisture . Subfloor conditions are associated with both subjective dampness and measured moisture. Insulation, ventilation and occupancy are associated with subjective dampness.